Eighteenth-century musical rhetoric and late Debussy - Wong, Chee Yean; Loo, Fung Chiat (HRMARS, 2024)
The complex relationship between Debussy's late compositions and 18th-century musical rhetoric challenges the prevailing notions that associating both traditions, often seen as irrelevant to Debussy's French style. However, historical sources suggest otherwise. A look into 18th-century literature underscores musical rhetoric as predominantly Germanic, potentially relevant to Debussy's works. The complex relationship between Debussy's late pieces and 18th-century musical rhetoric calls into question long-held beliefs that such rhetoric is exclusively associated with Germanic heritage, which is frequently viewed as incompatible with Debussy's French manner. However, historical records indicate differently. A examination at 18th-century literature reveals that musical rhetoric is largely Germanic, which might be pertinent to Debussy's compositions. Moreover, Henry Prunière's posthumous dedication to Debussy, emphasizing his French modernist identity while sidelining his late works, prompts a revaluation. This discrepancy between the legacy Debussy had intended for himself and what was given to him, at least in the years immediately following his death, invites reconsideration of the significance of 18th-century musical rhetoric in understanding the structural intricacies of his compositions. Through analysis of historical documents and his late works, a more nuanced understanding of his compositional techniques can emerge. It highlights the importance of incorporating 18th-century musical rhetoric to decipher the inherent structural complexities in his late works.